Simply constructed highly dispersed cobalt nanoparticles in diverse N-doped graphitic carbon with remarkable performances for water electrolysis. (19th July 2022) - Ji, Xiaochao; Bo, Lili; Zhang, Yuning; Shi, Wenping; Guan, Xiaolin; Xia, Liucheng; Shen, Yuxing; Wang, Yunxia; Tong, Jinhui
Abstract: Metal/carbon composite materials are highly promising electrocatalysts for water electrolysis. In this work, three composites of metal cobalt nanoparticles highly dispersed in N-doped carbon materials were facilely constructed by pyrolysis of different phenylenediamine based Schiff base-Co complexes (PDBs). Interestingly, the composites derived from PDBs based on different phenylenediamine exhibited different morphologies. The superior case is that rodlike composite catalyst was derived from o -phenylenediamine based PDBs. The obtained catalyst exhibited remarkable performances for both cathodic hydrogen evolution reaction (HER) and anodic oxygen evolution reaction (OER), as well as overall water electrolysis. Only 172 and 289 mV of overpotentials and 1.57 V of cell voltage were exhibited at 10 mA cm −2 for HER, OER and water splitting in 1.0 M KOH, respectively. The catalyst also displayed robust stability and high Faraday efficiency, and thus are potential high-performance catalyst for commercial water electrolysis. Graphical abstract: Image 1 Highlights: PhenylenediamineSchiff base-Co complexes were used as precursors. Catalysts derived from different phenylenediamine with different morphologies. Metal dispersity, N doping level and morphology were simultaneously improved. The catalysts exhibited high N-dopant level and defect density. The optimum catalyst exhibits high electrocatalytic activity for water splitting.